Bhutan Policy Note : Harnessing Spatial Opportunities in Agriculture for Economic Transformation - Dizon, Felipe; Jackson, Chris; Adubi, Abimbola; Taffesse, Samuel (World Bank, Washington, DC, 2019)
Home to over 735,000 people, the Kingdom of Bhutan has achieved rapid economic growth and poverty reduction, despite the constraints of being a small, landlocked, and mountainous country. Its neighbors, China to the north and India to the south, are in contrast the two most populous countries in the world. Bhutan’s land area is only 1 percent of India’s and 0.5 percent of China’s. Even surrounded by much larger economies, Bhutan has seen its economy expand rapidly in recent years, largely through hydropower exports to India and construction. The country halved its poverty rate to 12 percent between 2007 and 2012, and by 2017 it had achieved a further reduction, to 8.2 percent (NSB and World Bank 2017). National policy remains centered on diversifying export-led growth beyond hydropower exports to India and on making Bhutan’s economic growth more inclusive of all citizens. The agriculture sector, one of the five jewels in the Bhutanese economy, can play a key role in sustaining growth, reducing poverty, creating jobs, and expanding shared prosperity. Bhutan’s dense and virtually untouched forests, abundant water resources, and diversity of wild species are exceptional natural endowments, and correspondingly, environmental conservation is the cornerstone of Bhutan’s development approach (World Bank 2014). This Policy Note reviews Bhutan’s recent agricultural transformation from a spatial perspective and suggests measures to make further progress. The discussion focuses on crop-level drivers of productivity and spatial patterns of agricultural production in relation to markets, especially in relation to opportunities for expanding market potential to support the national development goals of the Royal Government of Bhutan (RGoB). The government has set targets in a number of policy areas where agriculture plays a critical role.